Modern weapons and military equipment for issue 4-2017 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2017)
Full speed ahead? Russia seeks to maintain momentum in shipbuilding program. Russia to Launch 2 Nuclear Subs in 2017. Beyond the Raptor and Lighting: World plays fifth-gen catch-up.